VAN DER VEEN, A. Maurits; "Ideas, Interests and Foreign Aid"; Cambridge University Press; New York, United States of America; 2011; pp. 290. ISBN: 978-0-521-26409-9 Paperback - Malafaia, Thiago Corrêa (Estudos Internacionais: revista de relações internacionais da PUC Minas, 2015)
Author: VAN DER VEEN, A. Maurits; "Ideas, Interests and Foreign Aid"; Cambridge University Press; New York, United States of America; 2011; pp. 290. ISBN: 978-0-521-26409-9 Paperback